Surveying the Effectiveness of General English vs ESP in Chemistry Education - Nailah Zakiyah Makarim; zalika luna bunga widati; wahyunengsih , wahyunengsih (Ikatan Dosen Menulis, 2025)
This study compares General English versus English for Specific Purposes (ESP) in academic and professional English proficiency. General English develops reading, writing, listening, and speaking skills, giving students a solid linguistic foundation. In contrast, ESP is tailored to specific communicative needs in domains such as science, business, and medicine, with a focus on vocabulary and structures relevant to professional or academic contexts. The research analyzes instructional strategies, effectiveness, and challenges associated with implementing both approaches. Recommendations are provided to help educators effectively integrate General English and ESP, thereby enhancing learners' language competence for academic success and career preparedness.